2012
DOI: 10.1097/bpo.0b013e318237c17e
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Ponseti Method in the Iranian Population

Abstract: Therapeutic level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 20 publications
1
49
0
6
Order By: Relevance
“…Failure of correction using the Ponseti is attributed mainly to lack of brace compliance, low parental educational level, severity of deformity and technical error in casting [14].…”
Section: Discussionmentioning
confidence: 99%
“…Failure of correction using the Ponseti is attributed mainly to lack of brace compliance, low parental educational level, severity of deformity and technical error in casting [14].…”
Section: Discussionmentioning
confidence: 99%
“…Colburn and Williams11) reported an initial correction rate of 95%. Moreover, other medical centers in different nations also reported that 92%-100% clubfeet in their patients, whose age at the time of presentation was usually less than 1 year, responded to initial manipulation and casting as described in the Ponseti protocol 1,6,10,12,13,14,15). Verma et al16) found that the Ponseti method was also effective in children between the ages of 1 to 3 years, and they reported an initial successful rate of about 89%.…”
Section: An Overview Of the Ponseti Methodsmentioning
confidence: 99%
“…The bar should be bent 5 to 10 degrees with the convexity away from the child to hold the feet in a valgus position and it should be of sufficient length so that the heels of the shoes are at shoulder width. The shoes maintain the foot in 10 to 15 degrees of dorsiflexion while wearing the brace 1,3,4,5,6,7,12,15,21,22,23,24). The foot appears to be over-corrected into abduction, but it is not a real overcorrection, but full abduction 24).…”
Section: An Overview Of the Ponseti Methodsmentioning
confidence: 99%
See 2 more Smart Citations